Compressibility behaviour of laterite soil treated with lime under saturated and unsaturated conditions - Ahmad Rizal, Nurin Hannah (2022)
In Malaysia, laterite soil is commonly employed as construction materials for roads, buildings, slopes and foundations as it is widely available. Besides, their nature as high durable soil makes them abundantly used in all geotechnical construction. However, some laterite soil is problematic due to its high clay content. Moreover, the climate conditions (annual flood and dry season) cause changes in soil suction in the unsaturated layer above the groundwater level, affecting the geotechnical structure performance. Therefore, quicklime (CaO) is used as a soil stabiliser with various percentages to enhance the strength and compressibility of natural soil, consequently extending the structure’s life span and functionality. This research aims to evaluate the strength and compressibility of lime-treated laterite, under saturated and unsaturated conditions. However, the main focus is more on soil compressibility behaviour. The optimum lime content and curing period are determined by the Unconfined Compressive Test (UCT), following the Malaysian Public Work Department (MPWD) for soil strength requirement on the stabilised subgrade. The strength of lime-treated soil had achieved the required minimum of 800 kPa at 5% lime content seven days curing period, denoted as 5%L7D sample. Next, based on California Bearing Ratio (CBR) testing, lime helps increase soil strength in unsaturated conditions but requires more curing time to build resilience to withstand the saturated conditions, which is inconvenient for real-world construction. The soil compressibility was tested via a conventional oedometer (saturated) and a suction-controlled oedometer under the axis-translation technique (unsaturated). In saturated conditions, the compressibility of laterite changes from high to moderate compressibility upon lime treatment. In unsaturated conditions, the effect of cementation bonding and suction is noticeable. The compressibility of laterite changes from high to low compressibility with increasing suction. According to the loading-collapse (LC) curve result, the suction effect was depicted by higher yield strength with higher matric suction. However, the effect of bonding showed a reduction in yield strength with increasing matric suction, which opposed the empirical concept proposed by Alonso et al. (1994). It was concluded that the effectiveness of lime is low in dry conditions (high matric suction).